A Review on Characterization Techniques for Carbon Quantum Dots and Their Applications in Agrochemical Residue Detection - John, Bony K.; Abraham, Thomas; Mathew, Beena (Journal of fluorescence, 2022)
Carbon quantum dots (CQDs) have emerged as one of the most promising nanomaterials in the carbon nanostructures family in recent years due to their low toxicity, simple synthetic methods, unique fluorescence emission, good photostability, excellent water solubility, high specific surface areas and outstanding electronic properties. They have thus been employed in a wide range of applications, including fluorescent sensing, electrochemical sensing, bioimaging, drug delivery, antimicrobial studies, antioxidants, and photocatalysis. CQDs drawn great interest in sensing applications due to their unique photochemical, electrochemical and electrochemiluminescence properties. They exhibit excitation wavelength-dependent or -independent photoluminescence (PL) behaviour, high quantum yield, and promising binding ability with analytes, which make them an ideal candidate for use in PL based sensing platforms. Excessive use of agrochemicals in farm fields can pollute the environment and have potentially adverse health effects on aquatic and human life. Since there are very few monitoring techniques are available for sensing such harmful substances, there is an urgent need to develop a sensor for the facile, rapid and on-site detection and quantification of agrochemical residues in the environment. Several CQD-based fluorophores for detecting agrochemical residues employing static or dynamic quenching processes have recently been published. The key quenching mechanisms involved in the sensing process include FRET, PET and IFE. The first part of this review intends to provide a comprehensive overview of various techniques to characterize CQDs such as UV–vis., FT-IR, PL, XRD, NMR, TEM, TGA, XPS and Raman analysis. In addition application of CQDs as fluorescent sensors for agrochemical residue in different media are summarized in this reiew. The LOD values and rapid action of the sensor demonstrates significant advantages of these methods over conventional analytical procedures. Graphical abstract